Effectiveness of Vitamin D Suplementation in Pregnant Women with Vitamin D Deficiency to Improved Fetal Biometry - Donel S.; Ruza Prima Rustam; Inayah Inayah; M. Yulis Hamidy; Ratu Astuti Dwi Putri; Machyuddin T.M Pangaribuan; Ahmad Fahruddin; Maya Savira (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Objective: The aim of this study was to determine the effect and effectiveness of vitamin D on fetal biometry.Method: This study was a Quantitative Study of two quasi-experimental groups. The research was conducted in Rupat District, Bengkalis Regency, Riau Province from June 2022 to August 2022. The research sample was pregnant women with vitamin D deficiency who were divided into an intervention group of 20 subjects and a control group of 20 subjects.Results: Examination of vitamin D levels in pregnant women and examination of fetal biometry was carried out. Then given a 1000 IU vitamin D supplement to pregnant women with vitamin D deficiency levels, re-evaluated after 3 months vitamin D levels in pregnant women and re-measured fetal biometry. There were significant differences in Fetal Biometrics between the pre-Intervention and post-Intervention studies in the intervention group with p=0.001. The intervention group also showed that there was an increase in the proportion of Normal Biometrics from 8 subjects before the intervention compared to 13 subjects after 3 months of vitamin D supplementation interventionConclusion: Vitamin D supplementation for 3 months in pregnant women with Vitamin D deficiency is proven to improve fetal health through Fetal Biometry examination.Efektivitas Suplemen Vitamin D dalam Meningkatkan Biometri Janin pada Wanita Hamil dengan Defisiensi Vitamin DAbstrakTujuan: Studi ini bertujuan mengetahui dampak dan efektivitas vitamin D terhadap biometri janin.Metode: Studi kuantitatif ini mengunakan dua grup dengan pendekatan kuasi-eksperimental. Penelitian ini dilaksanakan di Rupat, Kabupaten Bengkalis, Provinsi Riau dari Juni 2022 hingga Agustus 2022. Sampel penelitian ini adalah Wanita hamil dengan defisiensi vitamin D yang dibagi menjadi grup intervensi sebanyak 20 orang dan grup kontrol sebanyak 20 orang.Hasil: Dilakukan pengukuran kadar vitamin D pada Wanita hamil dan biometri janin. Pada grup intervensi diberikan suplementasi vitamin D 1000IU dan dievaluasi kembali kadar vitamin D setelah tiga bulan dan dilakukan kembali biometri janin. Terdapat perbedaan signifikan pada biometri janin sebelum dan sesudah intervensi dengan p=0.001. Grup intervensi juga menunjukkan peningkatan proprorsi biometri normal dari 8 orang menjadi 13 orang setelah tiga bulan suplementasi vitamin DKesimpulan: Suplementasi vitamin D selama tiga bulan pada Wanita hamil dengan defisiensi vitamin D terbukti membantu kesehatan janin melalui pemeriksaan biometri janin.Key words: Biometri, Defisiensi Vitamin D, Kehamilan